Conformity under uncertainty: Reliance on gender stereotypes in online hiring decisions. Issue 1 (26th February 2014) - Uhlmann, Eric Luis; Silberzahn, Raphael
Abstract We apply Bentley et al.'s theoretical framework to better understand gender discrimination in online labor markets. Although such settings are designed to encourage employer behavior in the northwest corner of Homo economicus, actual online hiring decisions tend to drift southeast into a "confirmation bias plus weak feedback loops" pattern of discrimination based on inaccurate social stereotypes.